A dual mode distributed economic control for a fuel cell– photovoltaic-battery hybrid power generation system based on marginal cost. (27th September 2019) - Yang, Hanqing; Li, Qi; Wang, Tianhong; Qiu, Yibin; Chen, Weirong
Abstract: Proton exchange membrane fuel cell system (PEMFCS) combining with photovoltaic and battery is now considered to be a promising alternative power generation. This paper presents a dual mode distributed economic control for a fuel cell-photovoltaic-battery hybrid power generation system (HPGS), which selects free control mode in normal situation, and the cooperative control mode is adopted when control precision declines or large state of charge (SoC) differences of battery energy storage devices (BESDs) appears. The droop control based on power generation cost by combining droop coefficient and marginal cost function considering line loss together is employed to minimize system power generation cost under free control mode. The system average voltage obtained by consensus algorithm is added to compensate bus voltage and reference power based on average marginal cost function considering line loss is calculated to correct output power under cooperative control mode. The challenge of further balancing SoCs of BESDs is implemented by internal control among BESDs. Results conducted on RT-LAB simulation platform verify effectiveness of the proposed method, indicating that cooperative control mode as a complementary way of free control mode can achieve economical operation of the studied HPGS, while maintaining bus voltage in reasonable range and balancing SoC. Highlights: Free control mode minimizes system power generation cost in normal situation. Cooperative control mode based on consensus algorithm is proposed. The proposed method can also balance SoCs of BESDs. Validity is analyzed through RT-LAB simulation results.